Effects of Surprisal and Entropy on Vowel Duration in Japanese. (March 2019) - Shaw, Jason A.; Kawahara, Shigeto
Research on English and other languages has shown that syllables and words that contain more information tend to be produced with longer duration. This research is evolving into a general thesis that speakers articulate linguistic units with more information more robustly. While this hypothesis seems plausible from the perspective of communicative efficiency, previous support for it has come mainly from English and some other Indo-European languages. Moreover, most previous studies focus on global effects, such as the interaction of word duration and sentential/semantic predictability. The current study is focused at the level of phonotactics, exploring the effects of local predictability on vowel duration in Japanese, using the Corpus of Spontaneous Japanese. To examine gradient consonant-vowel phonotactics within a consonant–vowel-mora, consonant-conditioned Surprisal and Shannon Entropy were calculated, and their effects on vowel duration were examined, together with other linguistic factors that are known from previous research to affect vowel duration. Results show significant effects of both Surprisal and Entropy, as well as notable interactions with vowel length and vowel quality. The effect of Entropy is stronger on peripheral vowels than on central vowels. Surprisal has a stronger positive effect on short vowels than on long vowels. We interpret the main patterns and the interactions by conceptualizing Surprisal as an index of motor fluency and Entropy as an index of competition in vowel selection.